Fatty Acid Composition, Antioxidant, and in vitro Anti-inflammatory Activity of Five Cold-Pressed Prunus Seed Oils, and Their Anti-biofilm Effect Against Pathogenic Bacteria - Fratianni, Florinda; d'Acierno, Antonio; Ombra, Maria Neve; Amato, Giuseppe; De Feo, Vincenzo; Ayala-Zavala, Juan Fernando; Coppola, Raffaele; Nazzaro, Filomena (Frontiers in Nutrition, 2021)
Background/Aim: Sweet almond (Prunus amygdalus dulcis) oil is one of the most famous cold-pressed seed oils. However, other species of Prunus can provide oils with healthy properties. We analyzed the fatty acid (FA) composition, as well as the antioxidant, the in vitro anti-inflammatory properties, and the antibiofilm activity of five commercial vegetable cold-pressed seed oils of apricot, peach, plum, cherry, and black cherry. Methods: Gas Chromatography-Mass Spectrometry was performed for the analysis of FAs The antioxidant property of the oils was carried using different tests [2, 2-diphenyl-1-picrylhydrazyl (DPPH assay)], Ferric Reducing Antioxidant Power (FRAP), and the 2, 20 -azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS·+). The denaturation assay performed on bovine serum albumin (BSA) was used to evaluate the in vitro anti-inflammatory activity. The anti-biofilm activity was assessed using five pathogenic strains, namely, Acinetobacter baumannii, Escherichia coli, Listeria monocytogenes, Pseudomonas aeruginosa, and Staphylococcus aureus, through the crystal violet test and the 3-(4,5-dimethylthiazol-2-yl)−2,5-diphenyltetrazolium bromide (MTT), used to evaluate the metabolism of the microbial cells present within the biofilm. Results: Oleic acid and linoleic acids were the most abundant FAs. Black cherry seed oil exhibited the best antioxidant activity, but in general, the amount of oil needed to inhibit the activity of 1 ml of DPPH assay at 50% did not exceed 10 μg. The extract concentration for the 50% inhibition of the denaturation of the protein (IC50) did not exceed 4.4 μg. Linoleic and stearic acids affected the antioxidant activity of the oils; oleic acid, linolenic, and palmitoleic acids exhibited beneficial effects in preserving the BSA denaturation, as shown by the correlation data. The oils were able to inhibit the biofilm formation of the pathogens (up to 71.40% of inhibition) as well as act against their mature biofilm, although with different strengths, with values up to 61.54%. Concurrently, they also acted on the pathogen metabolism. Conclusion: The oils represent a valuable source of some healthy FAs. They showed potential antioxidant and anti-inflammatory in vitro activity, in addition, their potential effect on the biofilm can offer important ideas for research and reflection on their use as functional foods and/or ingredients.